Discrete time branching processes in random environment - Kersting, Götz, 1950-; Vatutin, V. A. (Vladimir Alekseevich) (Mathematics and statistics series (ISTE). Branching processes, branching random walks and branching particle fields set, 2017)
Branching processes are stochastic processes which represent the reproduction of particles, such as individuals within a population, and thereby model demographic stochasticity. In branching processes in random environment (BPREs), additional environmental stochasticity is incorporated, meaning that the conditions of reproduction may vary in a random fashion from one generation to the next. This book offers an introduction to the basics of BPREs and then presents the cases of critical and subcritical processes in detail, the latter dividing into weakly, intermediate, and strongly subcritical regimes.